IMPULSIVE BUYING BEHAVIOR PERSPECTIVE OF MASLAHAH IMAM AL GHAZALI : STUDY ON SHOPPING BEHAVIOR OF VISITORS IN SOLO GRAND MALL SHOPPING CENTER - Zulfatus Sa’diah; Raisatul Karimah (STIT Sunan Giri Bima, 2023)
This phenomenon of impulsive buying, almost everyone must have done it consciously or not. One of the shopping centers, Solo Grand Mall, gets visitors reaching 10.0000 to 15.000 people every day while on weekends it reaches 20.000 in a day. The increasing tendency of people to shop at malls encourages sudden purchases. On the other hand, impulsive buying behavior tends to result in waste and this is contrary to the Islamic view of Maslahah. The majority of scholars discuss maslahah, one of which is Imam Al-Ghazali who is famous as Sufism. This research is a qualitative research (field research) by collecting data using observation, interviews and documentation, the data is then analyzed using an inductive method. The results of this study indicate that based on the characteristics of impulsive buying by visitors, the character of disregard for consequences is a characteristic that is very contrary to Imam Al-Ghazali's principle of maslahah in terms of fulfilling benefits. The types of impulsive buying that visitors are prohibited from being pure impulse types and blind buyers, because visitors tend to fulfill wants rather than needs and are very contrary to the maslahah of Imam Al-Ghazali in fulfilling kulliyat-al-khamsah.